Design and synthesis of novel (S)-Naproxen hydrazide-hydrazones as potent VEGFR-2 inhibitors and their evaluation in vitro/in vivo breast cancer models. (1st May 2021) - Han, M. İhsan; Atalay, Pınar; Tunç, Cansu Ümran; Ünal, Gökhan; Dayan, Serkan; Aydın, Ömer; Küçükgüzel, Ş. Güniz
Graphical abstract: Abstract: Naproxen is a common non-steroidal anti-inflammatory drug, which is the most usually used propionic acid derivative for the treatment of many types of diseases. In this study, a series of novel ( S )-Naproxen derivatives bearing hydrazide-hydrazone moiety were designed, synthesized, and evaluated for anticancer activity. The structures of these compounds were characterized by spectral ( 1 H– 13 C NMR, FT-IR, and HR-MS analyses) methods. All synthesized compounds were screened for anticancer activity against two different human breast cancer cell lines (MDA-MB-231 and MCF-7). Among them, ( S )-2-(6-methoxynaphthalen-2-yl)- N '-{( E )-[2-(trifluoromethoxy)phenyl]methylidene} propanehydrazide (3a) showed the most potent anticancer activity against both cancer cell lines with a good selectivity (IC50  = 22.42 and 59.81 µM, respectively). Furthermore, the molecular modeling of these compounds was studied on Vascular Endothelial Growth Factor Receptor 2. Inhibition of VEGFR-2 and apoptotic protein Bcl-2 was investigated in MDA-MB-231 cells treated with compound 3a by using Western Blotting. Apoptosis was also detected by staining with DAPI in fluorescence microscopy. Flow Cytometry analyses related to cell cycle phases showed that a dramatic increase in S and M phases was established compared to untreated control cells indicating the cancer cell cycle arrest. The anticancer activity of compound 3a was investigated in the Ehrlich acid tumor model, a well-validated in vivo ectopic breast cancer model, in mice. Our results showed that compound 3a had anticancer activity and decreased the tumor volume in both low (60 mg/kg) and high (120 mg/kg) doses in mice.